Strategi Implementasi Pendidikan Budi Pekerti Hindu Berbasis Kearifan Lokal di Desa Adat Kerobokan, Buleleng - Duwi Oktaviana (Jurnal Penelitian Agama Hindu, 2026)
Global cultural disruption and hedonistic lifestyles are triggering the moral degradation of the younger generation, necessitating a revitalization of the role of traditional institutions as bastions of values. This study aims to describe the community-based Hindu character education strategy in the Kerobokan Traditional Village, Buleleng, and analyze the process of internalizing these values ​​in the digital era. Applying qualitative methods with a descriptive-analytical approach, data collection was conducted through participatory observation of pasraman (traditional market) activities and ceremonies, in-depth interviews with village leaders (prajuru) and youth, and a documentary study of customary law (awig-awig). The results indicate that the implementation of character education takes place within an adaptive sociocultural ecosystem: the community functions as a More Knowledgeable Other, providing scaffolding through the Ngayah tradition; the implementation of anti-drug regulations (Pararem) as a critical cultural action to break the culture of silence, and the use of the Nyekar ritual as a participatory medium that instills egalitarian values. It concludes that the traditional village has successfully transformed from merely a guardian of tradition into an effective non-formal educational institution that balances physical rituals and communication technology. This study provides a scientific contribution in the form of a local wisdom-based pedagogical model that integrates the perspectives of social psychology, critical pedagogy, and media theory to strengthen national cultural identity.